(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Of the many great writers born in this age, Charies Dickens holds a special fascination for me. Perhaps, no other writer, has been able to depict so vividly, man’s social predicament This thesis not only tries to explore the impact of the Victorian underworld in major writers like Charles Dickens, but analyses the influence o f contemporary writers on his narrative art Crime, mystery and suspense are central to their art and thought - William Wilkie Collins, who is only now beginning to receive the recognition, which was long overdue, was one such writer. This study, which is also a comparison, tries to show how society influences and conditions man’s attitude to life. The Victorian underworld here is responsible for these two writers’ interest in crime and the criminal. Crime, mystery and suspense, are intrinsic to Dickens’s and Collins’s narrative art. A still more interesting aspect o f this study is the influence of one writer on another. Not only did Dickens and Collins, have the same kind o f commitment and dedication towards their art, but Collins was able to influence that great master with his skill at plot construction. He himself looked up to this great artist while at the same time encouraging Dickens towards more plausible plots. He, on the other hand, perfected his art o f characterization with Dickens’s approval. What endeared Collins to Dickens was his ability to assimilate and at the same time retain his individuality from the shadow o f the master’s muse.